Evaluating game-based teaching systems in economics courses - Iannace, Arturo Mariano; Bisanti, Matteo; Piazzoli, Andrea (Frontiers in Education, 2024)
The integration of games in education has garnered substantial interest. This study explores a gamebased teaching system, a prototype Megagame with RPG elements, within an Economics course. The theoretical analysis underscores the immersive potential of RPGs in educational contexts. Methodologically, we assessed the engagement of the course as a proxy for gauging the impact of the game on the learning process. The game involved 177 undergraduate students in thematic sessions, with 59 males and 118 females. Of these, only 114 filled out the pre-test, and 86 filled out the posttest, showing a dropout rate of 25%. The range of the age was between 19 and 21 years. We propose an evaluative framework through pre-post surveys. The results show a decrease in cognitive engagement and an increase in some elements of emotional engagement in students' perceptions, despite high starting expectations by students. Thus, this research highlights the need for a more effective use of gaming as an educational tool by identifying and addressing these shortfalls through further studies, and for the subsequent broader implementation of GBL techniques.